Reviewer - Journal of Infrastructure & Facility Asset Management (Journal of Infrastructure & Facility Asset Management, 2022)
Paper Writting StipulationPapers on JIFAM - The Journal of Infrastructure & Facility Asset Management Journal is regulated by general stipulation as follows.-          Papers must be a real work of the author.-          Papers has never been published in other media.-          Papers must contain discussion about Infrastructure & Facility Asset Management.-          Papers must contains a new discussion, judging based on the discussion that has been published in previous JIFAM.-          The paper has to take references from Scientific Journal with minimum of 5 papers.-          Paper lengths are limited in 8-16 pages.-          Paper Template can be downloaded on the website http://https://iptek.its.ac.id/index.php/jifamScope of TopicJIFAM accepts papers on Infrastructure & Facility Asset Management. The scope of the topic includes, but not limited, of  the following.-          I & F Function-          I & F Demand - Supply-          I & F User Behavior-          I & F Policy-          I & F Planning-          I & F Administration Aspects-          I & F Operation System-          I & F Maintenance System-          I & F Evaluation Technique-          I & F Disposal-          I & F Economical Aspect-          I & F Financial Aspect-          I & F Management Organization-          I & F Spatial Aspects and Environmental Aspects·      Mahendra A. Maulana,  Institut Teknologi Sepuluh Nopember (ITS), Surabaya, Indonesia·      Januarti Jaya Ekaputri, Institut Teknologi Sepuluh Nopember (ITS), Surabaya, Indonesia·      Trihanyndio Rendi Satrya, Institut Teknologi Sepuluh Nopember (ITS), Surabaya, Indonesia·      Djoko Legono, Institut Teknologi Sepuluh Nopember (ITS), Surabaya, Indonesia·      Anastasia Caroline Sutandi, Universitas Parahyangan, Bandung·      Hitapriya Suprayitno, Institut Teknologi Sepuluh Nopember (ITS), Surabaya, Indonesia·      Eko Budi Santoso, Institut Teknologi Sepuluh Nopember (ITS), Surabaya, Indonesia·      Satria Darmanegara, Institut Teknologi Sepuluh Nopember (ITS), Surabaya, Indonesia·      Mahendra A. Maulana,  Institut Teknologi Sepuluh Nopember (ITS), Surabaya, Indonesia·      Januarti Jaya Ekaputri, Institut Teknologi Sepuluh Nopember (ITS), Surabaya, Indonesia·      Trihanyndio Rendi Satrya, Institut Teknologi Sepuluh Nopember (ITS), Surabaya, Indonesia·      Djoko Legono, Institut Teknologi Sepuluh Nopember (ITS), Surabaya, Indonesia·      Anastasia Caroline Sutandi, Universitas Parahyangan, Bandung·      Hitapriya Suprayitno, Institut Teknologi Sepuluh Nopember (ITS), Surabaya, Indonesia·      Eko Budi Santoso, Institut Teknologi Sepuluh Nopember (ITS), Surabaya, Indonesia·      Satria Darmanegara, Institut Teknologi Sepuluh Nopember (ITS), Surabaya, Indonesia